Safety and efficacy of neublastin in painful lumbosacral radiculopathy: a randomized, double-blinded, placebo-controlled phase 2 trial using Bayesian adaptive design (the SPRINT trial). Issue 9 (September 2017) - Backonja, Miroslav; Williams, Leslie; Miao, Xiaopeng; Katz, Nathaniel; Chen, Crystal
Abstract : Abstract: Neublastin (BG00010) is a first-in-class, glial cell–derived neurotrophic factor shown in preclinical studies and an early clinical trial to have potential for the treatment of neuropathic pain. SPRINT was a phase 2, multicenter, double-blinded, placebo-controlled study to evaluate efficacy/safety of 5 neublastin doses (50, 150, 400, 800, and 1200 μg/kg) administered as an intravenous injection 3 times/week for 1 week in patients with chronic painful lumbosacral radiculopathy, utilizing Bayesian response-adaptive study design. Primary endpoint was change from baseline in mean 24-hour average general pain intensity over a 5-day period (week 1) after the last dose, analyzed using a Bayesian normal dynamic linear model. One hundred seventy-six patients were randomized and received treatment (placebo n = 48, 50 μg/kg n = 38, 150 μg/kg n = 13, 400 μg/kg n = 16, 800 μg/kg n = 20, 1200 μg/kg n = 41). Among the tested neublastin doses, the lowest dose (50 μg/kg) showed the greatest difference from placebo for change from baseline in mean average general pain intensity at week 1 after last dose, followed by the highest dose (1200 μg/kg) (posterior mean difference −1.36 [95% credible interval −2.22 to −0.52] and −0.75 [−1.59 to 0.08], respectively). Similar trends were observed in secondary efficacy endpoints. The most common adverse event in all neublastin dose groups was pruritus (79% vs 10% with placebo). There was no dose–response relationship with respect to primary/secondary efficacy outcomes or incidence of pruritus, despite dose-proportional increases in serum neublastin concentrations. In conclusion, while this study showed some evidence of pain relief with neublastin, particularly at the lowest dose, there was no clear dose–response relationship for pain reduction or the most common adverse event of pruritus. Abstract : Supplemental Digital Content is Available in the Text.Neublastin showed some evidence of pain relief among patients with painful lumbosacral radiculopathy; however, there was no clear dose–response relationship.